Polymorphic phase transitions: Macroscopic theory and molecular simulation - Anwar, Jamshed; Zahn, Dirk (Advanced Drug Delivery Reviews, 2017)
Transformations in the solid state are of considerable interest, both for fundamental reasons and because they underpin important technological applications. The interest spans a wide spectrum of disciplines and application domains. For pharmaceuticals, a common issue is unexpected polymorphic transformation of the drug or excipient during processing or on storage, which can result in product failure. A more ambitious goal is that of exploiting the advantages of metastable polymorphs (e.g. higher solubility and dissolution rate) while ensuring their stability with respect to solid state transformation. To address these issues and to advance technology, there is an urgent need for significant insights that can only come from a detailed molecular level understanding of the involved processes. Whilst experimental approaches at best yield time- and space-averaged structural information, molecular simulation offers unprecedented, time-resolved molecular-level resolution of the processes taking place. This review aims to provide a comprehensive and critical account of state-of-the-art methods for modelling polymorph stability and transitions between solid phases. This is flanked by revisiting the associated macroscopic theoretical framework for phase transitions, including their classification, proposed molecular mechanisms, and kinetics. The simulation methods are presented in tutorial form, focusing on their application to phase transition phenomena. We describe molecular simulation studies for crystal structure prediction and polymorph screening, phase coexistence and phase diagrams, simulations of crystal-crystal transitions of various types (displacive/martensitic, reconstructive and diffusive), effects of defects, and phase stability and transitions at the nanoscale. Our selection of literature is intended to illustrate significant insights, concepts and understanding, as well as the current scope of using molecular simulations for understanding polymorphic transitions in an accessible way, rather than claiming completeness. With exciting prospects in both simulation methods development and enhancements in computer hardware, we are on the verge of accessing an unprecedented capability for designing and developing dosage forms and drug delivery systems in silico, including tackling challenges in polymorph control on a rational basis.
EAM Import::2019-03-08